Antidiarrheal mechanism of Carpolobia lutea leaf fractions in rats - Nwidu, Lucky Lebgosi; Essien, Grace Emannuel; Nwafor, Paul Alozie; Vilegas, Wagner [UNESP] (Informa Healthcare, 2011)
Context: Carpolobia lutea G. Don (Polygalaceae) leaf is reputable as an antidiarrheal agent among the Efik and Ibibio tribe of Akwa Ibom State, Nigeria. The crude extract is reported to show antidiarrheal and antiulcer effects in rodents.Objective: The isolation and characterization of drug molecules from the leaf fraction with antidiarrheal bioactivity and determination of mechanism of action are reported.Material and methods: Gradient extraction by maceration yielding n-hexane, chloroform, ethyl acetate, and ethanol fractions (770 mg/kg) were used to establish the fractions suitable for drug discovery. The antidiarrheal effect of the leaf fractions of Carpolobia lutea was evaluated using castor oil-induced diarrhea, castor oil-induced intestinal transit, and enteropooling.Results: Results indicate that all fractions produced a significant (p < 0.01-0.001) decrease in castor oil-induced diarrhea in rats. This effect was not antagonized by isosorbide dinitrate (150 mg/kg, p.o), diphenoxylate (5 x 10(-3) mg/kg p.o) and yohimbine (1 mg/kg, s.c.) except for the chloroform fraction. The ethyl acetate fraction produced 100% inhibition of intestinal transit, an effect greater than pure drug. Phytochemical analysis of the ethyl acetate fraction yielded polyphenolic compounds.Conclusion: The leaf fractions contain two types of antidiarrheal agents, one mediating its effect through alpha(1) - presynaptic adrenoceptor while the other does not. Polyphenols isolated may in part lend credence for observed antidiarrheal activity.
Keywords: Carpolobia lutea; Polygalaceae; antidiarrheal; mechanism; isolation; polyphenols